Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Suppose you have the following operator: $$ \left( \frac{d}{dx}\circ x -1 \right), $$ where $\frac{d}{dx}\circ x$ means "multiply by $x$ and then take the derivative of the product". Applying this on $(\ln {x})^m$ gives $$ \left( \frac{d}{dx}\circ x -1 \right)(\ln x)^m= \frac{d}{dx} x (\ln x)^m - (\ln x)^m = (\ln x)^m + m(\ln x)^{m-1} - (\ln x)^m =m(\ln x)^{m-1} $$ This pretty much looks like $\frac{d}{dx}x^m=mx^{m-1}$. So I'm asking if $$ \frac{d}{d \ln{x}} = \left( \frac{d}{dx}\circ x -1 \right) $$ is true in general or just when I apply it on $(\ln x)^m$?

share|cite|improve this question
up vote 15 down vote accepted

Looks like it, because $$ \frac{d f(x)}{d \ln(x)} = \frac{df(e^t)}{dt} = e^t f'(e^t) = xf'(x) = f(x)+xf'(x)-f(x)=\frac{d(xf(x))}{dx} - f(x)$$

share|cite|improve this answer
ah cool thx and welcome to – draks ... Jan 10 '12 at 12:07

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.